P-2 Cookery group for bereaved adults. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Jackson, Matt; Ratcliffe, Kevin
Abstract : For three years St Richard's Hospice has run a successful cookery group for bereaved adults. The group started because it was identified that people struggled with cooking and eating in bereavement. Clients attend six sessions having the opportunity to cook a main course and a dessert under the guidance of the hospice head chef. The group then shared a meal they created together. It was evident from evaluations following initial groups that isolation, loneliness, loss of confidence and lack of self care are issues for bereaved people. They can lose interest in cooking or not have the confidence or skills to cook for themselves. Cooking and eating with others is a social event. When a loved one dies this opportunity is lost. The aim of the cookery group is to provide a safe place for people to meet other bereaved people to create an environment where trust and friendships develops and to gain pleasure and enjoyment from cooking. Through cooking and eating together the group found they are able to build trusting relationships with each other and build the confidence to talk about their loss. The challenge and pleasure that is created by learning, preparing and eating beautiful food together gives the clients much needed enjoyment and distractions from other pressures in their lives. They reported that their confidence and enjoyment of cooking grew, their overall diet improved and their social life blossomed as they began to have the confidence to invite family and friends round for dinner. Two of the groups continue to meet and have a 'come dine with me' at each others houses every month.